Inflow modeling for wind farm flows in RANS. Issue 1 (May 2021) - Laan, M. P. van der; Baungaard, M.; Kelly, M.
Abstract: Wind turbine interaction in wind farms can lead to energy loss and increased wind turbine loads, with the magnitude of these effects strongly depending on atmospheric conditions. One-dimensional Reynolds-averaged Navier-Stokes (RANS) models are able to represent the atmospheric boundary layer (ABL) over a range of model fidelity, and can be used for steady-state inflow profiles in three-dimensional RANS simulations of wind farms. In the present work, an overview of existing and recently developed atmospheric inflow models is presented. The inflow models are applied to separately demonstrate impacts on the velocity deficit of a row of ten wind turbines, due to: turbulence intensity and atmospheric stability in the atmospheric surface layer; ABL depth; and Coriolis-induced veer.